2020
DOI: 10.1088/2053-1591/ab66ee
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of reactive dye using heterogeneous photo-Fenton catalysts: ZnFe2O4 and GO-ZnFe2O4 composite

Abstract: Dyes, being potential pollutants, need alarming attention for their degradation from wastewater. Advanced oxidation processes (AOPs) are among the most effective methodology for the degradation of pollutants. In the present study, the heterogeneous photo-Fenton catalysts (ZnFe 2 O 4 and graphene oxide based ZnFe 2 O 4 composite) were prepared and used to study the degradation of synzol red reactive dye. The prepared catalysts were well characterized by using SEM, FTIR and XRD analysis. The effect of various pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(19 citation statements)
references
References 36 publications
(36 reference statements)
2
17
0
Order By: Relevance
“…All the characteristic peaks of g-C 3 N 4 and Ag 2 WO 4 are present in the Fe-doped ternary composite but with lesser intensities than the undoped CN-AW and Fe-CN composites. However, the strong intensity of diffraction peaks in both the composites suggests the successful synthesis and crystalline nature of composites [25]. ere is also a very slight shift of the peak at a diffraction angle of 2θ � 45.3 °, corresponding to a plane (402) towards higher diffraction angles, indicating the insertion of Fe into the host composite lattice.…”
Section: Xrd Analysismentioning
confidence: 94%
“…All the characteristic peaks of g-C 3 N 4 and Ag 2 WO 4 are present in the Fe-doped ternary composite but with lesser intensities than the undoped CN-AW and Fe-CN composites. However, the strong intensity of diffraction peaks in both the composites suggests the successful synthesis and crystalline nature of composites [25]. ere is also a very slight shift of the peak at a diffraction angle of 2θ � 45.3 °, corresponding to a plane (402) towards higher diffraction angles, indicating the insertion of Fe into the host composite lattice.…”
Section: Xrd Analysismentioning
confidence: 94%
“…The iron leaching of all catalysts, after each reusability run, was checked using atomic absorption spectroscopy, and the results obtained are presented in Table 1. The low iron leaching values (far below the European Union Standard i.e., 2.0 mg/L [12]) suggest that the heterogeneous catalysts are stable towards metal leaching from solid to liquid state. • As per EU directives, Fe leaching should not be higher than 2.0 ppm.…”
Section: Reusability and Stability Of Catalystsmentioning
confidence: 99%
“…Earlier, studies revealed that persistent organic pollutants have been treated with many conventional processes such as chemical, physical, and biophysical processes but proved inefficient. In recent years, effective and viable treatment technologies widely used were Advanced Oxidation Processes (AOPs) [11,12]. These Processes involve the in situ production of oxidizing species such as hydroxyl radicals ( • OH).…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of the heterogeneous Fenton process was improved by using the nanomaterial composed of ferric oxide, silica, and alumina (Nguyen et al, 2021). Degradation of Synozol Red reactive dye was achieved using ZnFe 2 O 4 catalyst and the composite prepared from ZnFe 2 O 4 and graphene oxide (Nadeem et al, 2020). Nanocomposites of goethite and akaganeite demonstrated photocatalytic activity by removing the color of Methyl Orange (Pal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%